Geochemical Characterization and Provenance Study of Ilmenites from Fluvial Sediments of River Cauvery in Parts of Tamil Nadu, Southern India - Vybhav, K; Prakash Narasimha; K. N., Pradeep; Pradeep, P. Mujumdar; R. Nagendra; N. Gobalakrishnan (International Journal of Economic and Environmental Geology, 2018)
The Cauvery river is the third longest flowing river in South India. This river flows through three southern Indian states (Karnataka, Tamil-Nadu and Puducherry). The river Cauvery takes its birth at a place called Talacauvery in the state of Karnataka, and after a long journey of 800 km from the Western-Ghats finally forms a delta and joins the Bay of Bengal in the east. This river traverses high grade metamorphic rocks. Ilmenites are good indicators of provenance and several researchers throughout the globe have contributed on this aspect. Present study is focused on chemical characterization of the detrital ilmenite from the fluvial sediments of downstream of the river Cauvery. The TiO2 content of ilmenites varies from 46.42 to 51.28 wt%, whereas iron oxide values range between 46.35-50.68 wt. %. The detrital ilmenite grains are primary in nature and have not subjected to any alteration. By chemistry we can conclude that basic suites are source for the ilmenites in fluvial sediments of river Cauvery.